Efektivitas Dan Kontribusi Pajak Reklame Terhadap Pendapatan Asli Daerah (PAD) di Kota Medan - Maristella J Lumbanbatu; Kumala Dewi; Sorta Lumbantoruan (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of the study was to determine the effectiveness of billboard tax revenue on the Regional Original Revenue of Medan City in 2019-2021 and to find out how much the contribution of billboard tax to the Original Revenue of Medan City in 2019-2021. The research uses qualitative methods that are descriptive. The types and sources of data used are primary data and secondary data. Data analysis techniques are summarizing data, presenting data, analyzing data, and preliminary conclusions that are temporary. The results showed that the effectiveness rate in 2019-2021 achieved every year was not significant, namely 44.26% for 2019; 16.69% for 2020; and 100% for 2021. The average effectiveness of billboard tax revenue on Local Original Revenue for 3 years is 53.77% or can be categorized as